BUDAYA ORGANISASI DAN STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA - Nurmitasari, Jeki; Utami , Esti Margiyanti; Rahmawati, Fitri (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2023)
This study aims to examine the effect of organizational culture and also work stress on organizational commitment through job satisfaction. The population in this study were employees of Perumda BPR Bank Purworejo. The sample selection technique used purposive sampling with a total sample of 54 respondents. Measuring tool for data collection using a questionnaire with a Likert scale. Data analysis uses Hierarchical Regression Analysis. The results of data analysis prove 1) organizational culture has a positive influence on organizational commitment 2) work stress has a negative effect on organizational commitment 3) organizational culture has a positive influence on job satisfaction 4) work stress has a negative effect on satisfaction 5) job satisfaction has a positive effect on organizational commitment 6) job satisfaction partially mediates the effect of organizational culture on organizational commitment 7) job satisfaction fully mediates the effect of job stress on organizational commitment